Design and optimization of multi user OFDM orthogonal chaotic vector shift keying communication system - Ansam M. Abed; Fadhil S. Hasan (Institute of Advanced Engineering and Science, 2021)
This paper study and present, power allocation strategy on sub-carriers of multiuser OFDM employed for orthogonal chaotic vector shift keying (MU OFDM-OCVSK) over multipath frequency selective fading channels. firstly, the MU OFDM-OCVSK system is modeled with power allocated on reference and information bearing subcarriers. Then, the computed bit error rate equation of the power allocation MU OFDM-OCVSK system is derived. The optimal power allocation strategy on subcarriers is obtained using convex optimization. Finally, compared with the traditional MU OFDM-DCSK and MU OFDM-OCVSK without power allocation system the proposed system can achieve an excellent BER performance under multipath Rayleigh fading channels. Numerical and Simulation results emphasize the remarkable features of the proposed optimal power allocation strategy.